Farinacciella ramalhoi, n. gen., n. sp., a larger foraminifer from the Kimmeridgian – lower Tithonian of the Neo -Tethyan realm - Cherchi, Antonietta; Radoičić, Rajka; Schroeder, Rolf (Journal of Mediterranean Earth Sciences, 2016)
A new larger foraminifer Farinacciella ramalhoi , n. gen., n. sp., from the Upper Jurassic of several regions of the Neo-Tethys is described: Mount Vojnik (Crna Gora/Montenegro), Lepini and Aurunci Mountains (Latium, Italy), Murcia province (Spain) and Arrabida area (Portugal).The test of this dimorphic calcareous microgranular taxon is made up of two morphologically and structurally different stages of growth: the probably megalospheric forms exhibit a juvenile conical stage with trochospirally arranged chambers. This is followed by a compressed adult stage with a cuneiform to ?reniform-circular outline. The juvenile stage in the centre of the large discoidal microspheric forms, which is made up of irregularly coiled chambers, is followed by predominantly annular chambers. Farinacciella ramalhoi, which is placed in the family Valvulinidae Berthelin, 1880, was previously assigned by several authors to Kilianina lata Oberhauser, 1956, but differs clearly from this taxon.